Lycii radicis cortex alleviates fibrosis in hiPSC-derived multilineage hepatic organoids via the cAMP-PKA pathway - Xu, Junming; Sang, Xiaopu; He, Yongfei; Ke, Jie; Xu, Jiasen; Liu, Tanbin; Wang, Jicai; Zhai, Hang; Chen, Xiaoni; Shi, Xianjie; Wu, Fenfang (Frontiers in Pharmacology, 2025)
BackgroundLiver fibrosis, driven by excessive extracellular matrix (ECM) deposition and activation of hepatic stellate cells (HSCs), still lacks effective therapies, partly due to the absence of human-relevant models. Lycii Radicis Cortex (LRC), a traditional Chinese medicine, exhibits reported anti-inflammatory and antioxidant activities, yet its anti-fibrotic potential has not been validated in human organoid-based systems.MethodsWe established hiPSC-derived multilineage hepatobiliary organoids (mHBOs) containing mesoderm-derived HSCs and implemented a TGF-β–induced fibrosis model within this platform. Using mHBOs alongside a CCl4-injury mouse model, we assessed the anti-fibrotic activity of LRC, and investigated underlying mechanisms.ResultsLRC significantly attenuated fibrosis in mHBOs and in CCl4-injured mice, reducing ECM accumulation and HSC activation. In mHBOs, LRC activated the cAMP–PKA–CREB pathway, thereby suppressing HSC activation and reducing parenchymal apoptosis; these effects were reversed by PKA inhibition.ConclusionLRC exhibits potent anti-fibrotic activity in a physiologically relevant human organoid model, providing mechanistic insight into HSC regulation and supporting its potential as a candidate therapy for chronic liver disease. Furthermore, this study introduces a translational platform integrating animal models and hiPSC-derived organoids to facilitate anti-fibrotic drug discovery and evaluation.